Safe-Shields: Basal and Anti-UV Protection of Human Keratinocytes by Redox-Active Cerium Oxide Nanoparticles Prevents UVB-Induced Mutagenesis - Francesca Corsi; Erika Di Meo; Daniela Lulli; Greta Deidda Tarquini; Francesco Capradossi; Emanuele Bruni; Andrea Pelliccia; Enrico Traversa; Elena Dellambra; Cristina Maria Failla; Lina Ghibelli (MDPI AG, 2023)
Cerium oxide nanoparticles (nanoceria), biocompatible multifunctional nanozymes exerting unique biomimetic activities, mimic superoxide-dismutase and catalase through a self-regenerating, energy-free redox cycle driven by Ce3+/4+ valence switch. Additional redox-independent UV-filter properties render nanoceria ideal multitask solar screens, shielding from UV exposure, simultaneously protecting tissues from UV-oxidative damage. Here, we report that nanoceria favour basal proliferation of primary normal keratinocytes, and protects them from UVB-induced DNA damage, mutagenesis, and apoptosis, minimizing cell loss and accelerating recovery with flawless cells. Similar cell-protective effects were found on irradiated noncancerous, but immortalized, p53-null HaCaT keratinocytes, with the notable exception that here, nanoceria do not accelerate basal HaCaT proliferation. Notably, nanoceria protect HaCaT from oxidative stress induced by irradiated titanium dioxide nanoparticles, a major active principle of commercial UV-shielding lotions, thus neutralizing their most critical side effects. The intriguing combination of nanoceria multiple beneficial properties opens the way for smart and safer containment measures of UV-induced skin damage and carcinogenesis.